PREDICTING FINANCIAL DISTRESS OF PUBLIC COMPANIES LISTED IN AMMAN STOCK EXCHANGE - Al-khatib, Hazem B .; Al-Horani, Alaa (European Scientific Journal, ESJ, 2012)
This study investigates the role of a set of financial ratios in predicting financial distress of publicly listed companies in Jordan. Using Logistic Regression and Discriminant Analysis a comparison has been made between the two models to determine which is more appropriate to use as well as which of the financial ratios are statistically significant in predicting the financial distress of Jordanian companies. During the period 2007 to 2011, the results show that both logistic regression and discriminant analysis can predict financial distress, and that Return on Equity (ROE) and Return on Assets (ROA) are the most important two financial ratios, which help in predicting the financial distress of public companies listed in Amman stock Exchange.